Public Sector Accounting Fraud: What Do We Know, What is Missing, and Where to Go Next? A Systematic Review - Sri Widodo; Wiyasto Dwi Handono; Hari Purnama (MUQADDIMAH: Jurnal Ekonomi, Manajemen, Akuntansi dan Bisnis, 2026)
This study presents a systematic literature review of public sector accounting fraud to identify the geographical distribution of publications, the most influential journals, trending research topics, and future research agendas. The review followed the PRISMA 2020 methodology, initially identifying 742 records from databases, which were screened based on publication years (2021–2025) and subject area relevance, resulting in 54 studies included in the final analysis. The findings reveal that Asia, particularly Indonesia (37 articles), dominates global publication volume, with developing countries collectively contributing 58% of total output, surpassing developed countries (32%). The most influential journals in the last five years include COGENT BUSINESS AND MANAGEMENT and the JOURNAL OF FORENSIC ACCOUNTING RESEARCH. Trending topics include fraud detection, fraud prevention, forensic accounting, whistleblowing, and integrating the fraud triangle with internal control and audit quality. Future research agendas should focus on strengthening the link between whistleblowing and forensic accounting, incorporating organizational studies into fraud prevention models, and developing cross-country comparative studies. This study acknowledges limitations in database coverage, citation-based impact metrics, and geographical bias stemming from Indonesia dominance.